ENHANCING MOBILITY: DEVELOPING A PEDESTRIAN SOLUTION FOR LOCOMOTION CHALLENGES AND ROAD SAFETY - Aneta WNUK; Dagmara JANKOWSKA-KARPA (Transport Problems)
Orthopedic crutch attachments (caps) are an important but underestimated element supporting the safety of pedestrians, including elderly road users with disabilities. A review of the literature shows that this topic is rarely the subject of research and new solutions. In 2022, the multidisciplinary team of the Motor Transport Institute started multi-stage work to develop and implement innovative multi-functional attachments to orthopedic equipment as an element improving the comfort of movement of this group in various weather conditions. Focus group interviews with potential users, which were a part of the project, indicated the most important features of the selection of such a solution, such as material, anti-slip properties, ease of replacement, durability (low abrasion), ensuring stability, and quiet operation. On this basis, the final prototype of the orthopedic crutch attachment presented in the article was developed. In addition, areas related to road safety and pedestrian safety devices were identified, the implementation and promotion of which could improve the functioning of orthopedic equipment users.